The Japanese economy in retrospect selected papers - Saxonhouse, Gary R. (World Scientific studies in international economics, 2010)
Gary R Saxonhouse was one of the world's leading scholars on Japanese economy. Born in New York City in 1943, he attended Yale University, where he received his PhD in Economics in 1971. In 1970, he joined the Faculty of Economics at the University of Michigan, where he remained throughout his career. The selection of his published papers that comprises this two-volume publication is a testimony and tribute to his remarkable accomplishments and influence, which were cut short by his untimely death in November 2006, following a battle with leukemia. Volume I contains a selection of his published papers that have been instrumental in enhancing the understanding of Japan's modern economic history, focusing particularly on the Japanese cotton-spinning industry. Volume II features a selection of his published papers that look at how Japan's technology and innovation were key in promoting Japan's economic success; how its economy was shaped by its comparative advantage and related policies; and how its macro-financial policies were implemented in the course of its economic growth after World War II.